Modifying Surface Charges of a Thermophilic Laccase Toward Improving Activity and Stability in Ionic Liquid - Stevens, Joseph C.; Shi, Jian (Frontiers in Bioengineering and Biotechnology, 2022)
The multicopper oxidase enzyme laccase holds great potential to be used for biological lignin valorization alongside a biocompatible ionic liquid (IL). However, the IL concentrations required for biomass pretreatment severely inhibit laccase activity. Due to their ability to function in extreme conditions, many thermophilic enzymes have found use in industrial applications. The thermophilic fungal laccase from Myceliophthora thermophila was found to retain high levels of activity in the IL, [C2C1Im][EtSO4], making it a desirable biocatalyst to be used for lignin valorization. In contrast to [C2C1Im][EtSO4], the biocompatibility of [C2C1Im][OAC] with the laccase was markedly lower. Severe inhibition of laccase activity was observed in 15% [C2C1Im][OAc]. In this study, the enzyme surface charges were modified via acetylation, succinylation, cationization, or neutralization. However, these modifications did not show significant improvement on laccase activity or stability in [C2C1Im][OAc]. Docking simulations show that the IL docks close to the T1 catalytic copper, likely interfering with substrate binding. Although additional docking locations for [OAc]- are observed after making enzyme modifications, it does not appear that these locations play a role in the inhibition of enzyme activity. The results of this study could guide future enzyme engineering efforts by showing that the inhibition mechanism of [C2C1Im][OAc] toward M. thermophila laccase is not dependent upon the IL interacting with the enzyme surface.